Large scale screening for benzimidazole resistance mutations in Nematodirus battus, using both pyrosequence genotyping and deep amplicon sequencing, indicates the early emergence of resistance on UK sheep farms. (April 2020) - Melville, Lynsey A.; Redman, Elizabeth; Morrison, Alison A.; Rebecca Chen, Pai Chia; Avramenko, Russell; Mitchell, Sian; Van Dijk, Jan; Innocent, Giles; Sargison, Fiona; Aitken, Catriona; Gilleard, John S.; Bartley, Dave J.
Abstract: Benzimidazoles (BZ) have been the anthelmintic of choice for controlling Nematodirus battus infections since their release in the 1950s. Despite heavy reliance on this single anthelmintic drug class, resistance was not identified in this nematode until 2010 (Mitchell et al., 2011). The study aimed to explore the prevalence of BZ-resistance mutations in N. battus from UK sheep flocks using deep amplicon sequencing and pyrosequencing platforms. Based on evidence from other gastrointestinal nematodes, resistance in N. battus is likely to be conferred by single nucleotide polymorphisms (SNP) within the β-tubulin isotype 1 locus at codons 167, 198 and 200. Pyrosequencing and deep amplicon sequencing assays were designed to identify the F167Y (TTC to TAC), E198A (GAA to GCA) and F200Y (TTC to TAC) SNPs. Nematodirus battus populations from 253 independent farms were analysed by pyrosequencing; 174 farm populations were included in deep amplicon sequencing and 170 were analysed using both technologies. F200Y was the most prevalent SNP identified throughout the UK, in 12–27% of the populations tested depending on assay, at a low overall individual frequency of 2.2 ± 0.6% (mean ± SEM, based on pyrosequencing results). Four out of the five populations with high frequencies (>20%) of the F200Y mutation were located in NW England. The F167Y SNP was identified, for the first time in this species, in four of the populations tested at a low frequency (1.2% ± 0.01), indicating the early emergence of the mutation. E198A or E198L were not identified in any of the isolates. Results obtained were comparable between both techniques for F200Y (Lins' CCC, r c  = 0.96) with discrepancies being limited to populations with low frequencies. The recent emergence of resistance in this species will provide a unique opportunity to study the early stages of anthelmintic resistance within a natural setting and track its progress in the future. Graphical abstract: Image 1 Highlights: Early emergence of benzimidazole (BZ) resistance in Nematodirus battus . F200Y mutation most prevalent SNP identified. First identification of F167Y mutation associated with BZ resistance in Nematodirus . Good agreement between deep amplicon sequencing and pyrosequencing platforms.